Steam-Based Learning Bibliometric Analysis: Opportunities in Indonesian Language Teaching Research - Imam Safi'i; Ade Hikmat; Lili Wahdini; Asep Jejen Jaelani (IKIP PGRI Bojonegoro, 2024)
STEAM is a holistic learning approach and is one of the learning models that emphasizes the learning system in Indonesia in the 2013 Curriculum and the Merdeka Curriculum. This study aims to explore various research issues related to the implementation of STEAM in learning. Data collection was carried out using the Publish or Perish application which was sourced from Google Scholar and Scopus metadata with the keywords STEAM Based Learning and STEAM-based Learning from 2020 to 2023. Data analysis was carried out using the VOSviewer bibliometric. The results showed that the highest number of publications with Google Scholar metadata sources occurred in 2021 and 2022, namely 20 article titles. The highest number of publications from Scopus metadata sources is in 2021. Research opportunities related to the use of STEAM in learning Indonesian are still very high because there are no research topics related to the use of STEAM in learning Indonesian.